The role of physical activity in the treatment of depression - Siemko, Jakub; Rulewska, Natalia Maria; Grabowski, Filip; Neska, Dagmara; Prystacka-Szar, Dominika; Stadler-Szajda, Justyna; Czyżnikiewicz, Adrianna; Stołowski, Wenancjusz; Bujak, Magdalena; Waśniowska, Magdalena (Journal of Education, Health and Sport, 2025)
Introduction: Depression contributes significantly to the overall global societal and personal burden of disease. Despite the developments in treatment strategies, the effectiveness of both medication and psychotherapy is not optimal. As theoretical knowledge expands, so does the need for other practical evidence-based interventions. Among them, physical activity (PA) shows a potential therapeutic role. Aim: The aim of this article is to explore the role of PA in the treatment of depression and establish whether it is reasonable to think of physical exercise as a therapeutic intervention in a clinical setting. Review methods: A comprehensive analysis of research papers available on PubMed and Google Scholar was undertaken using the search terms encompassing the following keywords: depressive symptoms / depression / neuropsychiatry / physical activity / exercise / physical health / running therapy / treatment. Conclusion: Physical activity is known to help improve mental health. Exercise therapy is therefore a valuable option in mental health care, both in terms of mental and physical health, and should be considered standard practice for people with depression and/or anxiety disorders. All types of PA and exercise are beneficial. Putting an emphasis on this element of lifestyle when developing intervention plans, treatment programs, and health policy guidelines plays a key factor in providing a multi-dimensional approach to mental healthcare.